MATRIMONIAL CONVENTION - DAN LUPAŞCU (Challenges of the Knowledge Society, 2013)
The matrimonial regime is ruled by two perspectives, the Roman law and the German one. The Romanian concepts were taken from the French law. The new Romanian Civil Code is characterized by the special attention it pays to the regulation of spouses' patrimonial relationships, ant it therefore abandons the exclusivist conception and enacts several matrimonial regimes, namely: a) the regime of legal community; b) the regime of separation of assets; c) the regime of separation of assets with participation to acquisitions; d) the regime of conventional community. The matrimonial convention represents the legal document by which future spouses, or, as the case may be, current spouses, resorting to the liberty they have been conferred by the legislator, determine their own matrimonial regime or, as the case may be, modify their applicable matrimonial regime.